Analisis Kemampuan Ekoliterasi Dan Karakter Peduli Lingkungan Kelas IV SD Negeri 2 Bumirejo - Selvi Kurnianingsih; Nurhidayati Nurhidayati; Nur Ngazizah (Journal on Education, 2024)
Education can be done through education that leads the personality to have awareness and concern for its environment. This research aims to 1) determine the ecoliteracy abilities of students in class IV of SD Negeri 2 Bumirejo, 2) determine the environmentally caring character of students in class IV of SD Negeri 2 Bumirejo. This type of research uses descriptive qualitative research methods. The subjects of this research were class IV students with a total of 27 students, with samples taken from 5 students who were selected using purposive sampling determined by the researcher. Data collection techniques in this research used questionnaires, interviews, field notes and documentation to collect information. The results of the research showed that in 1) students' ecoliteracy abilities with cognitive aspects, there was 1 subject at sufficient criteria, 3 subjects at good criteria, and 1 subject at very good criteria, in the affective aspect there was 1 subject at adequate criteria and 4 subjects at very good criteria, in the psychomotor aspect there was 1 subject in the adequate criteria and 4 subjects in the very good criteria. 2) the character of caring for the environment in the indicator of sorting types of waste and the indicator of energy saving habits, there is 1 subject with good criteria and 4 subjects with very good criteria.